A comparative study on the release behavior of self-healing capsules under different asphalt mixing and transportation conditions. (19th September 2022) - Wang, Huoming; Peng, Zhen; Wu, Jie; Liu, Quantao; Zhao, Feiyang; Wan, Pei
Highlights: Damage of the capsules during mixing, transportation and compaction was studied. Capsules showed good mechanical and thermal resistances after mixing and transportation. Capsules maintained the original shape after mixing, transportation and compaction. Oil release ratios after compaction were 5.8% and 10.4% for WMA and HMA. Abstract: Calcium alginate capsules used in asphalt mixtures for crack healing is a promising maintenance approach for asphalt pavements. However, the effects of asphalt mixing and transportation on the properties of the capsules are unclear. In order to understand the damage of the added capsules during mixing, transportation and compaction, this research explored the healing agent release rate and change of the properties of the capsules within asphalt mixtures mixed and formed at different temperatures. Three-dimensional spatial distribution and breakage rate of capsules in asphalt mixtures were characterized by an X-ray microscope computed tomography. The capsules picked out of the mixtures were subjected to a series of experiments to study the microstructure, thermal stability, oil content and mechanical strength of the capsules before and after mixing, simulated transportation and compaction. In addition, the release rate of the healing agent during the mixing, transportation and compaction of the asphalt mixtures were also characterized through FTIR test on the extracted asphalt binder. The results showed that the capsules can be uniformly distributed in asphalt concrete after mixing, simulated transportation and compaction and maintained a similar shape to the original capsules. Meanwhile, both the mechanical resistance and thermal stability of the capsules after mixing and transportation met the production requirements of asphalt mixtures. The release rate of the healing agent from capsules during the mixing, transportation and compaction process of the warm mix asphalt was less than 6%, while the thermal action during the transportation simulation of hot mix asphalt doubled the healing agent release rate of the capsules within asphalt mixture.